POLA KEMITRAAN DINAS SOSIAL KOTA SEMARANG DENGAN RUMAH PINTAR BANGJO DALAM PENDAMPINGAN ANAK JALANAN - Jelita Natalia Simatupang; Puji Astuti (Journal of Politic and Government Studies, 2026)
This study examines the assistance of street children in Semarang City through partnership relations between the government and non-governmental organizations. The Semarang City Social Affairs Office holds authority in the provision of social welfare; however, as a single actor, it faces limitations in terms of budget, resources, and field coverage across all segments of society. Therefore, the government establishes a collaborative relationship with Rumah Pintar Bangjo as a platform through which street children can grow and develop optimally. This research employs a descriptive qualitative approach, with data collected through interviews, observation, and documentation. The informants in this study consist of nine individuals, including assisted children, representatives of the Semarang City Social Affairs Office, and Rumah Pintar Bangjo. Data analysis was conducted through data reduction, data display, and verification of the final conclusions. The findings indicate that the partnership model has been implemented quite effectively; however, gaps remain in the aspect of obstacle management. Therefore, the government, together with non-governmental organizations, must implement more intensive parental development initiatives and enhance the monitoring of child assistance to ensure the sustainability of the partnership program.